REKOMENDASI KEBIJAKAN SEWA RAHIM DARI PERSPEKTIF HAM DI INDONESIA - Valentia Berlian Ayu Febrianti; Budiarsih Budiarsih (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The development of technology in the field of reproduction has led to efforts to get pregnant outside the natural way. However, the rapid development of medical technology is not matched by legal developments. The focus of the research is on how important the rent of the womb is in Indonesia and how to recommend the policy of renting the womb from a human rights perspective. This study uses the Literature Study method and the Legislative Approach as well as the Conceptual Approach whose sources are taken from several relevant books and journals, taken from Google Scholar and the website. The next step is to analyze it to get a recommendation. The results of the study found that the practice of surrogate mothers or also known as uterine rental is an effort to realize the goal in the household, namely to have children, but the study provides recommendations that the act of renting a womb must be special and there are strong reasons to justify it, so there needs to be a special regulations regarding the practice of surrogacy in order to avoid a vacuum of norms